Comparison of Fatigue Analysis Results in the Frequency Domain using PSD data and speciβic load - Joon Jang; Jae Myung Cho; Won Woong Lee; Woo Chun Choi (Journal of ICT, Design, Engineering and Technological Science, 2019)
This study investigated the axial sensitivity of the aircraft structure to fatigue. Fatigue analysis for an aircraft needs to be done during a design stage to prevent fatigue failure during operation. Fatigue analysis can be done in a time domain or a frequency domain, and frequency domain analysis is more frequently used. Frequency domain analysis for an aircraft normally uses PSD data translated from the vibration experienced for its whole lifetime. If vibration information is insufficient in the PSD, it is supplemented by adding specific loads. In this study, the analysis was done using the PSD data with 7 different additional loads. The life was sensitive to the magnitude and direction of the load, and some loads increase the life. It was found that the aircraft structure is safe from fatigue failure. Since the fatigue test has not yet been carried out, further testing should be done. Also, further study will investigate how to quantify the sensitivity ratio of direction and magnitude of loads under various conditions.